Downregulation of GLS2 in glioblastoma cells is related to DNA hypermethylation but not to the p53 status. Issue 9 (10th August 2015) - Szeliga, Monika; Bogacińska‐Karaś, Małgorzata; Kuźmicz, Katarzyna; Rola, Radosław; Albrecht, Jan
Abstract : Human phosphate‐activated glutaminase (GA) is encoded by two genes: GLS and GLS2 . Glioblastomas (GB) usually lack GLS2 transcripts, and their reintroduction inhibits GB growth. The GLS2 gene in peripheral tumors may be i) methylation‐ controlled and ii) a target of tumor suppressor p53 often mutated in gliomas. Here we assessed the relation of GLS2 downregulation in GB to its methylation and TP53 status. DNA demethylation with 5‐aza‐2′‐deoxycytidine restored GLS2 mRNA and protein content in human GB cell lines with both mutated (T98G) and wild‐type (U87MG) p53 and reduced the methylation of CpG1 (promoter region island), and CpG2 (first intron island) in both cell lines. In cell lines and clinical GB samples alike, methylated CpG islands were detected both in the GLS2 promoter (as reported earlier) and in the first intron of this gene. CpG methylation of either island was absent in GLS2 ‐expressing non‐tumoros brain tissues. Screening for mutation in the exons 5–8 of TP53 revealed a point mutation in only one out of seven GB examined. In conclusion, aberrant methylation of CpG islands, appear to contribute to silencing of GLS2 in GB by a mechanism bypassing TP53 mutations. © 2015 Wiley Periodicals, Inc.